Issues Facing Cooperative Education in Institutions of Higher Education in the United States. Research Monograph, Number 2 - Stull, William A.; Utah State Univ., Logan ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Due to the expansion of cooperative education programs, critical issues facing them were examined. The issues as perceived by cooperative education directors were identified, along with their relative importance as perceived by directors and their immediate supervisors. The study aimed to determine whether differences exist between directors and their supervisors, between two- and four-year college directors, and among directors in the six regions of the United States. Separate research questionnaires were used for each of the two reference groups to ascertain directors' background (title, years in position, gender, age, institutional type, and name of immediate supervisor), as well as attitudes toward issues. A panel of expert judges refined the issues list, and a Likert-type scale was developed for the refined list of 55 issue statements. A second issues questionnaire was then administered to the supervisors and compared with the findings from the survey of directors. Conclusions include the following: a majority of directors expressed concern for maintaining the quality of cooperative education work assignments with an increasing number of institutions and students participating; the why and how of awarding and applying cooperative education credit is a very important issue; one factor scale, "Organizational Placement and Institutional Integration," showed differences between the co-op directors and their supervisors; the design of the cooperative education experience and award of credit is perceived as more important on the two-year college level; and there seem to be no discernible differences among regions. Among the suggestions for further study are: causes for the low proportion of female directors, cost effective methods, planning elements that increase the potential for success, and benefits of faculty involvement. Appendices include the director's and supervisor's issues questionnaires and a list of the panel of experts. (LC)
Availability: Research Committee, Cooperative Education Association, Cooperative Education Research Center, Northeastern University, Boston, MA 02115 ($5.75).
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: G007901614.
Educational level discussed: Higher Education.
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Keywords: Administrator Attitudes; Administrator Characteristics; College Credits; Colleges; Comparative Analysis; Cooperative Education; Cooperative Programs; Educational Administration; Educational Quality; Experiential Learning; Females; Higher Education; Program Effectiveness; Program Evaluation; Quality Control; Two Year Colleges; Reports, Research; Tests/Questionnaires.